Ca 2+ releases E‐Syt1 autoinhibition to couple ER‐plasma membrane tethering with lipid transport - Bian, Xin (2018)
The extended synaptotagmins (E-Syts) are endoplasmic reticulum (ER) proteins that bind the plasma membrane (PM) via C2 domains and transport lipids between them via SMP domains. E-Syt1 tethers and transports lipids in a Ca2+-dependent manner, but the role of Ca2+ in this regulation is unclear. Of the five C2 domains of E-Syt1, only C2A and C2C contain Ca2+-binding sites. Using liposome-based assays, we show that Ca2+ binding to C2C promotes E-Syt1-mediated membrane tethering by releasing an inhibition that prevents C2E from interacting with PI(4,5)P2-rich membranes, as previously suggested by studies in semi-permeabilized cells. Importantly, Ca2+ binding to C2A enables lipid transport by releasing a charge-based autoinhibitory interaction between this domain and the SMP domain. Supporting these results, E-Syt1 constructs defective in Ca2+ binding in either C2A or C2C failed to rescue two defects in PM lipid homeostasis observed in E-Syts KO cells, delayed diacylglycerol clearance from the PM and impaired Ca2+-triggered phosphatidylserine scrambling. Thus, a main effect of Ca2+ on E-Syt1 is to reverse an autoinhibited state and to couple membrane tethering with lipid transport.